Abundance of non-native crabs in intertidal habitats of New England with natural and artificial structure - Christina M. Lovely; Nancy J. O’Connor; Michael L. Judge (PeerJ, 2015)
Marine habitats containing complex physical structure (e.g., crevices) can provide shelter from predation for benthic invertebrates. To examine effects of natural and artificial structure on the abundance of intertidal juvenile crabs, 2 experiments were conducted in Kingston Bay, Massachusetts, USA, from July to September, 2012. In the first experiment, structure was manipulated in a two-factor design that was placed in the high intertidal for 3 one-week periods to test for both substrate type (sand vs. rock) and the presence or absence of artificial structure (mesh grow-out bags used in aquaculture, ∼0.5 m2 with 62 mm2 mesh openings). The Asian shore crab, Hemigrapsus sanguineus, and small individuals of the green crab, Carcinus maenas, were observed only in the treatments of rocks and mesh bag plus rocks. Most green crabs were small (<6 mm in carapace width) whereas H. sanguineus occurred in a wide range of sizes. In the second experiment, 3 levels of oyster-shell treatments were established using grow-out bags placed on a muddy sand substrate in the low intertidal zone: mesh grow-out bags without shells, grow-out bags with oyster shells, and grow-out bags containing live oysters. Replicate bags were deployed weekly for 7 weeks in a randomized complete block design. All crabs collected in the bags were juvenile C. maenas (1–15 mm carapace width), and numbers of crabs differed 6-fold among treatments, with most crabs present in bags with live oysters (29.5 ± 10.6 m−2 [mean ± S.D.]) and fewest in bags without shells (4.9 ± 3.7 m−2). Both C. maenas and H. sanguineus occurred in habitats with natural structure (cobble rocks). The attraction of juvenile C. maenas to artificial structure consisting of plastic mesh bags containing both oyster shells and living oysters could potentially impact oyster aquaculture operations.